Schoolteachers, Technologies of the Self, and the Genealogy of the Late Modern Subject: The Bulletin of the Queen's Summer School Association, 1915–1932. - McLean, Scott; Knox, Erin (Journal of Canadian Studies, 2025)
From the 1920s through the 1960s, thousands of Canadian schoolteachers spent much of their summer holiday period attending courses organized by universities or provincial departments of education. In the 1920s, Queen's University attracted students from every Canadian province to attend summer school in Kingston, Ontario. Through a content analysis of one hundred messages written by schoolteachers from across Canada, this article analyzes a technology of the self deployed in an effort to encourage other schoolteachers to enrol at Queen's University. The authors of these messages divided schoolteachers into two camps: those who were progressive, industrious, and ambitious and others. They positioned themselves and their readers as subjects with the responsibility of choosing the camp to which they belonged. This article decentres the study of power in the history of teacher education by analyzing how schoolteachers themselves governed schoolteachers. It demonstrates that technologies of the self are linked to the material interests of those who deploy them. The article furthers the genealogical study of late modern subjectivities by demonstrating that technologies of the self, which position human subjects as reflexive and autonomous beings responsible for shaping their own lives through conscious choices, were highly developed in the early twentieth century in Canada.